ChemInform Abstract: Asymmetric Aldol—Tishchenko Reaction of Sulfinimines. Issue 13 (March 2016) - Foley, Vera M.; McSweeney, Christina M.; Eccles, Kevin S.; Lawrence, Simon E.; McGlacken, Gerard P.
Abstract: The first example of an aldol—Tishchenko reduction of imines is reported.